Heat transfer in oscillating flow through porous medium with dissipative heat - Guria, M. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, heat transfer in flow between two horizontal parallel porous plates through a porous medium when the upper plate oscillates in its own plane has been analyzed taking into account the effect of viscous dissipation. An increment in the Prandtl number or Reynolds number results in an increment of the temperature profile. With an increase in viscous dissipative heat the temperature distribution decreases.
Keywords: injection; suction; transverse sinusoidal; transpiration cooling; viscous dissipation